International Partnership in Russia Conclusions from the Oil and Gas Industry - Henderson, James; Ferguson, Alastair; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
International Partnership in Russia provides a unique insight into the joint ventures formed by international oil companies in Russia during the post-Soviet era. It outlines the highs and lows in their fortunes and analyses the reasons for their successes and failures.
Keywords: Environmental economics; Industrial organization; Regional economics; Spatial economics; Development economics; International economics; Economic growth; Environmental Economics; Industrial Organization; Regional/Spatial Science; Development Economics; International Economics; Economic Growth